KESEJAHTERAAN RUMAH TANGGA PETANI KRATOM (Mytragina sp) DI KELURAHAN KEDAMIN HULU KECAMATAN PUTUSSIBAU SELATAN KABUPATEN KAPUAS HULU - Roslinda, Emi; Taqwa, Takhta M; Destiana, Destiana (Universitas Tanjungpura, 2025)
The kratom plant (Mitragyna sp.) is one of the non-timber forest products that grow abundantly in Kalimantan; it grows wild and is also widely cultivated. Kratom is a potential plant. The aim of the research is to calculate farmers' income from cultivating kratom and non-kratom plants, calculate farmer household expenses, and assess the welfare of kratom farmer households. This research used a survey method, with the research location purposively selected. Research data collection techniques are interviews, observation, and documentation. The method used in analyzing research data is a quantitative description. The results of data analysis show that the largest household income comes from on-farm, namely, income from the use of kratom, amounting to IDR 287,505,000. Household expenditure on food was IDR 84,885,000, and non-food IDR 42,385,000. Expenditures for financing farming amounted to IDR 82,508,000. The farmer household purchasing power (DBPP) is 2.4. The average farmer household exchange rate (NTPRP) is greater than one (NTPRP = 1.62). Keywords: farmer, income, kratom, Kedamin Hulu, welfare. Abstrak Tanaman kratom (Mitragyna sp) adalah salah satu hasil hutan bukan kayu yang tumbuh subur di Kalimantan dan tumbuh liar kratom juga banyak dibudidayakan. Kratom merupakan tanaman yang potensial. Tujuan penelitian adalah menghitung pendapatan petani dari usaha budidaya tanaman kratom dan bukan kratom, menghitung pengeluaran rumah tangga petani, menilai kesejahteraan rumah tangga petani kratom. Penelitian ini dilakukan dengan metode survey dimana lokasi penelitian ditetapkan secara sengaja (purposive). Teknik pengumpulan data penelitian adalah wawancara, observasi, dan dokumentasi. Metode yang dilakunan dalam menganalisis data penelitian adalah deskripsi kuantitatif. Hasil analisis data menunjukkan pendapatan rumah tangga terbesar berasal dari on-farm, yaitu pendapatan dari pemanfaatan kratom sebesar Rp287.505.000. Pengeluaran rumah tangga untuk pangan sebesar Rp84.885.000 dan non-pangan sebesar Rp42.385.000. Pengeluaran untuk pembiayaan usahatani sebesar Rp82.508.000. Daya beli rumah tangga petani (DBPP) sebesar 2,4. Nilai tukar rumah tangga petani (NTPRP) rata-rata lebih besar dari satu (NTPRP = 1,62). Kata kunci: petani, pendapatan, kratom, Kedamin Hulu, kesejahteraan